Henry S. Saunders collection of Walt Whitman papers - Saunders, Henry Scholey, 1864-1951.; Whitman, Walt, 1819-1892.
Letters and postcards (1887-1892) from Walt Whitman to John Johnston and J.W. Wallace of Bolton, England. Also includes correspondence of Richard M. Bucke and Horace Traubel; a memoir (1915) of Whitman written by Saunders; and a series of greeting cards (1911-1923) sent by Saunders and his wife Georgina utilizing poems and quotations of Whitman, Traubel, and others.
Collection material in English.
Described, in part, in: Walt Whitman : a catalog based upon the collections of the Library of Congress. Washington, D.C. : 1955.
Keywords: Bucke, Richard Maurice, -- 1837-1902 -- Correspondence; Johnston, John, -- 1852-1927 -- Correspondence; Traubel, Horace, -- 1858-1919 -- Correspondence; Wallace, J. W. -- 1853-1926 -- Correspondence; American poetry; Poetry